Metal Complexes with Zwitterionic Amino‐bis(methylcarboxyl) Group Expand Life‐Span of Aluminum Electrolyte Capacitor. Issue 32 (24th August 2018) - Ozawa, Masashi; Sugiue, Ayako; Akiyama, Kaori; Nishizaka, Miki; Suzuki, You; Sugaya, Tomoaki; Seii, Atsushi; Sakakura, Masao; Kamebuchi, Hajime; Tadokoro, Makoto
Abstract: This paper investigates a new metal complex that expands the life‐span of an insulator thin‐film formed from anodically‐oxidized alumina in an aluminum electrolyte capacitor. The insulator thin‐film was generally unstable in an electrolytic water solution because of hydrate dissolution. However, in an electrolytic solution containing H2 PO4 – ions and the organic acid diethlenetriamine‐N, N, N', N', N̋, N̋‐pentaacetic acid (H5 dtpa), the life‐span of the insulator thin‐film was remarkably expanded to more than 10000 h because the protective membrane on the anodic alumina electrode was stabilized. The stabilization effects of two complexes, [Ga III (H2 dtpa)(H2 O)] (1 ) and [In III (Hdtpa)Na(H2 O)3 ] (2 ), were investigated using leak current, 31 P‐NMR, and ESI‐TOF‐mass measurements. In1 only, the life‐span of the anodic alumina electrode expanded, while in2, an electrical connection through the insulator thin‐film due to hydrate dissolution caused a rapid explosive release of hydrogen gas. The differences in these results were attributed to the free amino‐ bis (methylcarboxyl) group in1, which recognized H2 PO4 – to form a protective alumina membrane. Abstract : This paper investigates a new metal complex that expands the life‐span of an insulator thin‐film formed from anodically‐oxidized alumina in an aluminum electrolyte capacitor. The different results were attributed to the free amino‐ bis (methylcarboxyl) group, which recognized H2 PO4 – as ternary adducts to form a protective alumina membrane.